Synthesis of densely functionalized pyrroles from unprotected carbohydrates - Xia, Mengxin (Nanyang Technological University, 2023)
Carbohydrates are important feedstock owing to their huge natural abundance, cheap price, and interesting properties. Compared with traditional fossil fuels, carbohydrates are suitable for synthesizing heterocycles because they are rich in functional groups such as hydroxyl, aldehyde, ketone, amino, and carboxylic acid moieties. Carbohydrates are considered as sustainable materials, and therefore, their direct conversion to various intermediates is of industrial relevance. Pyrroles are a class of nitrogen heterocycles with diverse bioactivities including anti-inflammatory, anti-bacterial, anti-cancer, and anti-oxidative properties. The activity of pyrrole-based drugs is tuned with the type of substituents on the pyrrole core and on the substitution pattern on the core pyrrole ring. Therefore, huge attention has been paid to synthesizing suitably functionalized pyrroles. Although several syntheses have been successfully developed for pyrroles, green, cheap, and sustainable pyrrole synthesis methods are highly desired. In this work, green and practical methods using carbohydrates as the starting material for pyrrole synthesis will be explored and developed. In Chapter One, an overview of carbohydrates and their usage as feedstocks was provided. A description of pyrroles and their use as drug compounds was included. Additionally, several pyrrole syntheses were introduced along with comments on their advantages and disadvantages. In Chapter Two, unactivated carbohydrates, oxoacetonitriles, and ammonium acetate were combined in one-pot reaction to produce densely functionalized pyrroles in yields ranging from 75-96%. Novel pyrrolo-glycosides were produced via disaccharides. This Et3N-catalyzed three-component reaction proceeded with exclusive chemo-, regio- and stereo-selectivities. It showed a wide substrate scope with high atom-economy and worked well at a 2-gram scale, indicating the possibility of large-scale synthesis. The functional groups on the pyrrole ring allows for the creation of more complicated compounds. The reaction proceeded through cascade mechanism comprising a few intermediates elucidated from mass spectrometry analysis. This work represents a significant step forward in the sustainable synthesis of densely functionalized pyrroles from inexpensive and easily accessible carbohydrates. In Chapter Three, a one-pot, three-component reaction between unprotected sugars, primary amines, and 3-oxoacetonitriles gave N-substituted 2,3,5-functionalized pyrroles or N-substituted 2,3,4-functionalized pyrroles in excellent yields. The selectivity of the reaction is easily controlled by altering the order in which substrates are added. Different kinds of sugars, primary amines, and oxoacetonitriles all reacted easily demonstrating a wide substrate scope. The research provides a straightforward procedure for incorporating nitrogen into sugars to create important N-heterocyclic molecules that can be further modified to make natural products and drug intermediates. In Chapter Four, N-substituted 2-amino-3-cyanopyrrole key framework was synthesized by combining unprotected carbohydrates, malononitrile, and primary amines in one-pot in up to 86% yield. This AcOH-catalyzed multicomponent reaction occurred under mild conditions in EtOH at 60 oC within 2 hours. It tolerated a broad substrate scope and worked smoothly on large scale (4 g). The usefulness of the synthesized pyrroles was demonstrated by converting their functional groups into other XVI versatile moieties. The reaction proceeded through a cascade mechanism as suggested by NMR and LC-MS experiments. The reaction methodology demonstrates a simple upcycling of carbohydrates to highly functionalized N-heterocyclic compounds. In Chapter Five, the reaction between α-hydroxyketones, oxoacetonitriles, and primary amines selectively gave N-substituted 2,3,5-functionalized 3-cyanopyrroles in up to 90% isolated yields. Here again, the reaction demonstrated broad substrate scope, proceeded under mild conditions (AcOH as a catalyst, EtOH, 70 oC, 3 h) and worked also on a large gram scale. Single-crystal X-ray diffraction and NMR experiments confirmed the structures of the 3-cyanopyrroles. The reaction can proceed through three pathways demonstrating the reactivity of the starting materials. Overall, the dissertation focuses on developing novel one-step multicomponent selective synthesis of suitably substituted pyrrole from cheap carbohydrates. The protocols developed in this thesis provide various choices for synthesizing pyrroles with different substituents and different substitution pattern from both aldoses and ketoses. Large-scale reactions and excellent yields show the potential for these reactions to be practical at the industrial scale. The usefulness of the synthesized pyrroles was demonstrated for the synthesis of robust intermediates that can be used for the synthesis of drug candidates. The possible reaction pathways to obtain the pyrroles have been studied deeply using NMR and LC-MC to provide evidence for the mechanistic speculations presented in the literature. It is our hope that this can be realized one day to contribute to saving our planet.